MODEL HUBUNGAN ENTREPRENEURIAL LEADERSHIP, ENTREPRENEURIAL CULTURE DAN ENTREPRENEURIAL MIND-SET TERHADAP ORGANIZATIONAL PERFORMANCE MELALUI INNOVATION SEBAGAI VARIABEL MEDIASI - Perkasa, Didin Hikmah; Abadi, Ferryal (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose-The main objective of this research is to study and analyze entrepreneurial leadership, entrepreneurial culture and entrepreneurial mindset on organizational performance with innovation as mediation using quantitative descriptive. Design/methodology/approach-Data were obtained from 280 respondents who are furniture entrepreneurs in DKI Jakarta. Data analysis in this study uses an alternative method of structural equation modeling (SEM)partial least square (PLS). Findings-The results show that entrepreneurial leadership and entrepreneurial mindset have a significant effect on organizational performance, but not for entrepreneurial culture. Innovation is proven to mediate the relationship between entrepreneurial culture and entrepreneurial mindset to organizational performance. Implications-Efforts to improve organizational performance can be implemented by encouraging entrepreneurial leadership and entrepreneurial mindset through a series of ongoing training. Keywords: entrepreneurial leadership, entrepreneurial culture, entrepreneurial mindset, innovation and organizational performance